Application Value of Novel Inflammatory Indicators in Response to Ursodeoxycholic Acid Therapy in Patients with Primary Biliary Cholangitis - Liu S; Pang Y; Wang X; Lin R; Tunala S (International Journal of General Medicine)
Siqi Liu,1 Yongli Pang,2 Xiaoxi Wang,3 Ruihang Lin,4 Siqing Tunala5 1Inner Mongolia Medical University, Hohhot, Inner Mongoli, People’s Republic of China; 2Ordos second People’s Hospital, Ordos, Inner Mongoli, People’s Republic of China; 3People’s Hospital of Ordos Dongsheng District, Ordos, Inner Mongoli, People’s Republic of China; 4Ordos Central Hospital, Ordos, Inner Mongoli, People’s Republic of China; 5Ordos Mongolian Medicine Hospital, Ordos, Inner Mongoli, People’s Republic of ChinaCorrespondence: Siqing Tunala, Ordos Mongolian Medicine Hospital, Ordos, Inner Mongoli, People’s Republic of China, Email tutu88600@126.comObjective: To analyze the application value of novel inflammation indicators such as the lymphocyte/monocyte ratio (LMR), neutrophil/lymphocyte ratio (NLR), and platelet/lymphocyte ratio (PLR) in patients with primary biliary cholangitis (PBC) undergoing ursodeoxycholic acid (UDCA) treatment. We plan to further seek simple and convenient methods to assess the response of patients to UDCA treatment.Methods: We recorded routine blood tests, liver function, and vitamin D (VD) levels of PBC patients and healthy controls visiting the hospital between October 2022 and October 2023. LMR, NLR, and PLR were calculated, and differences between the two groups were analyzed. PBC patients were divided into good response and poor response groups according to the Paris I criteria, and differences in laboratory tests between the two groups were analyzed. The predictive value of novel inflammation indicators in UDCA treatment response was further analyzed using ROC analysis.Results: LMR and VD levels were significantly lower in the PBC group compared to the control group (P=0.000, P=0.000). In PBC patients, the good response group had higher LMR than the poor response group (P=0.001) and lower NLR than the poor response group (P=0.015). The areas under the ROC curve for LMR and NLR were 0.682± 0.049 and 0.630± 0.052, respectively. There was a significant negative correlation between PLR and VD in PBC patients (r=− 0.252, P=0.005).Conclusion: Low LMR and high NLR may indicate poor treatment response. And PLR also have certain predictive values for treatment response.Keywords: primary biliary cholangitis, lymphocyte/monocyte ratio, neutrophil/lymphocyte ratio, platelet/lymphocyte ratio, vitamin D